BANYAKNYA PENJUALAN BBM DENGAN MENGGUNAKAN POM MINI TANPA DILENGKAPI IZIN DI KECAMATAN MUARA WAHAU KABUPATEN KUTAI TIMUR - SUYANTO, HARIS (Journal of Law ( Jurnal Ilmu Hukum ), 2018)
ABSTRACT Fuel oil is one of the vital elements needed to serve the needs of the general public both in poor countries, developing countries and even in countries that have developed countries.In East Kutai Regency itself, the Pom Mini business has increasingly grown, it can be found easily. The unclear rules of the government in writing also made more and more Pom Mini sellers found in East Kutai Regency. Although some of them claimed to have pocketed business licenses from the village head and RT / RW. The sale of Pom Mini fuel is not according to the law, because it does not comply with the standards listed in Law Number 2 of 1981 concerning Legal Metrology and Oil and Gas PerBPH Number 6 of 2015.The government is expected to pay more attention to the needs of society today. It would be nice to immediately issue special rules regarding the Pom Mini business so as not to cause confusion and weak oversight of all community business activities. Keywords: Fuel oil, Mini Pom